Court of swans [large type] - Dickerson, Melanie (Thorndike Press Large Print Christian Romance, 2024)
In medieval England, after her seven brothers are falsely accused of murder and treason, eighteen-year-old Delia flees their cruel stepmother and becomes a seamstress at Westminster Palace, hoping to gain their release, with Sir Geoffrey's assistance.